Implementasi Supervisi Klinis Dalam Meningkatkan Kualitas Pembelajaran IPAS di SD Negeri 5 Bowong Kecamatan Bungoro Kabupaten Pangkep - Indriani, Mulyani; W, Muhammad Fahreza; Syarifuddin, Syarifuddin (CV. Rayyan Dwi Bharata, 2026)
This study aims to describe in depth the implementation of clinical supervision in Science and Social Studies (IPAS) learning at SD Negeri 5 Bowong. Furthermore, it analyzes the role of clinical supervision in enhancing learning quality, specifically in addressing low student motivation and the limitations of teachers in utilizing innovative media and integrating science and social process skills.The research utilized a qualitative method with a case study approach. The study was conducted at SD Negeri 5 Bowong during the odd semester of the 2025/2026 academic year. Key informants included the principal, supervisors, three IPAS teachers, and students. Data collection techniques involved direct observation, semi-structured interviews, and documentation. Data validity was tested through credibility tests using triangulation of sources, techniques, and time, while data analysis followed an interactive model involving data reduction, data display, and conclusion drawing. The results indicate that the implementation of clinical supervision at SD Negeri 5 Bowong is carried out through a structured cycle including pre- observation (planning), observation, and post-observation (feedback) using collaborative and reflective models. Clinical supervision successfully improved IPAS learning quality by transforming teaching methods from conventional to active inquiry and Project-Based Learning, as well as encouraging the use of interactive digital media. The impact of these improved pedagogical practices is evident in escalated student motivation, increased active participation in group discussions, and the students' ability to independently construct knowledge through real investigation (HOTS).